PRODUÇÃO DE HORTALIÇAS COM UTILIZAÇÃO DE BANCADA DE CULTIVO HIDROPÔNICO DE BAIXO CUSTO - ARAÚJO, Thales Oliveira,; SERON, Cassio de Castro,; VENDRUSCOLO, Eduardo Pradi,; MARTINS, Murilo Battistuzzi,; SILVA FILHO, Marcelo Xavier,; LEONEL, Eduardo Augusto Souza, (ANAIS DO ENIC, 2024)
-